2017
DOI: 10.1002/ddr.21385
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Inflammatory and Analgesic Activities of Terminalia Muelleri Benth. (Combretaceae)

Abstract: Preclinical Research The anti-inflammatory and analgesic activities of a polyphenol-rich fraction (TMEF) obtained from Terminalia muelleri Benth. were measured. The analgesic activity of TMEF was tested using acetic acid-induced writhing and hot plate models in mice. The anti-inflammatory activity was assessed using carrageenan-induced paw edema model by measuring PGE , TNF-α, IL-1β, and IL-6 plasma levels as well as the paw thickness. TMEF was tested at doses of 100, 200, and 400 mg/kg p.o. and diclofenac sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…Vitexin was isolated from the ethyl acetate soluble fraction of E. speciosa leaves methanol extract. The compound was identified by physical data analyses and comparison to the reported literature . The UV absorption data indicated the presence of a flavone nucleus .…”
Section: Resultsmentioning
confidence: 99%
“…Vitexin was isolated from the ethyl acetate soluble fraction of E. speciosa leaves methanol extract. The compound was identified by physical data analyses and comparison to the reported literature . The UV absorption data indicated the presence of a flavone nucleus .…”
Section: Resultsmentioning
confidence: 99%
“…Swelling or edema, one of the cardinal signs of acute inflammation, is an important parameter to be considered when testing compounds with a potential anti‐inflammatory activity (Morris, ). Edema is a biphasic process, following carrageenan injection, serotonin and histamine release occurs within 1 hr, whereas the release of proteases, bradykinins and prostaglandins occurs within 2 and 3 hr, respectively (Fahmy, Al‐Sayed, Abdel‐Daim, & Singab, ; Ghosh, Chattopadhyay, Mandal, Kaity, & Samanta, ). Based on the results of this study, ECG was found to possess a significant anti‐inflammatory activity, as evidenced by the inhibition of carrageenan‐induced paw edema all over the experimental period with the maximum inhibition after 180 min.…”
Section: Discussionmentioning
confidence: 99%
“…TMEF pretreatment reduced the edema thickness by 48, 53, and 62% at the tested doses, respectively. TMEF administration inhibited the carrageenan-induced elevations in PGE2 (by 34, 43, and 47%), TNF-α (18, 28, and 41%), IL-1β (14, 22, and 29%), and IL-6 (26, 31, and 46%) [166].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%